Educational needs of patients with multiple sclerosis (MS) - Sahebozamani, M; Rashvand, F; Alavi- Majd, H; Moshtagh-e-Eshgh, Z (Advances in Nursing & Midwifery, 2009)
Background With respect to different problems and complications of patients with multiple sclerosis (MS), appropriate educational programs and interventions should be performed for them to promote their quality of life. Purpose This descriptive study was conducted to identify educational needs of patients who were the members of Iranian MS Society in 2007. Methods 174 subjects referring to the society were selected with convenience sampling method. A questionnaire in 4 parts was used for data collection. Results Most subjects (26.4%) were between 32-39, women (71%) as well as married (59.8%) and history of the disease less than 3 years (27.7%). 39.1% was in great need of education, 0.6% of disease nature, 94% of sexual disorders and 64.8% of administrative problems. A significant relationship was found between educational needs concerning physical issues and education (P=0.027) and also these needs and times of hospitalization (P=0.004). Conclusion It can be concluded that the most urgent educational needs were about sexual problems, mobility problems and administrative problems and the lowest need for education was about elimination problems. Keywords: Educational needs, Multiple sclerosis, Iranian Multiple Sclerosis Society. Physical needs.